2014
DOI: 10.1093/pasj/psu005
|View full text |Cite
|
Sign up to set email alerts
|

Broad-band spectroscopy of Hercules X-1 with Suzaku

Abstract: Hercules X-1 was observed with Suzaku in the main-on state from 2005 to 2010. The 0.4–100 keV wide-band spectra obtained in four observations showed a broad hump around 4–9 keV in addition to narrow Fe lines at 6.4 and 6.7 keV. The hump was seen in all the four observations regardless of the selection of the continuum models. Thus it is considered a stable and intrinsic spectral feature in Her X-1. The broad hump lacked a sharp structure like an absorption edge. Thus it was represented by two different spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…We have shown that the X-ray spectrum of Her X-1 during the high state contains strong evidence of blueshifted wind absorption. The Fe K band of the spectrum by itself could be explained by an array of Fe emission lines (at 6.4, 6.7, 6.97 keV) rather than by absorption features (Asami et al 2014). However, the N vii, O viii and Ne x regions unambiguously show blueshifted absorption lines at the same systematic velocity, thus confirming that we are observing an ionised wind.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We have shown that the X-ray spectrum of Her X-1 during the high state contains strong evidence of blueshifted wind absorption. The Fe K band of the spectrum by itself could be explained by an array of Fe emission lines (at 6.4, 6.7, 6.97 keV) rather than by absorption features (Asami et al 2014). However, the N vii, O viii and Ne x regions unambiguously show blueshifted absorption lines at the same systematic velocity, thus confirming that we are observing an ionised wind.…”
Section: Discussionmentioning
confidence: 96%
“…Such velocities are unlikely to occur in this system given that the accretion disc of Her X-1 is likely truncated by the magnetic field of the neutron star at ∼1000 R G . Asami et al (2014) consider different possible origins of the width of the line including line blending, comptonisation from an accretion disc corona or Doppler broadening but do not find a plausible explanation.…”
Section: Continuum Modellingmentioning
confidence: 96%
“…Fürst et al fit a number of different continuum models and we compare our fit to their "HighE" cutoff power law model from their Table 3. For the "narrow" iron line, Fürst et al (2013) found an energy centroid of E(FeKα n ) = 6.601 +0.017 −0.016 keV and σ(FeKα n ) = 0.25 +0.04 Asami et al (2014) found in their analysis of Suzaku data alone from Her X-1 that their spectral fits required a broad line in the 4−9 keV energy range. They suggested a number of possible physical origins for this feature but their data was not sufficient to attribute the line emission to one unique mechanism.…”
Section: Iron Emissionmentioning
confidence: 97%
“…Further spectral observations with better instruments have improved the measurement of the spectrum and included partial covering absorption (e.g. [20]). That the precessing accretion disk produces both the 35-day light-curve and the 35-day cycle in pulse shape changes was confirmed by [21].…”
Section: New Results In the Past 10 Yearsmentioning
confidence: 99%